(untitled) - David Cross (New York, 1992)
This book consists of four parts. Part One covers the most fundamental instruction skills and procedures. Part Two deals with a range of lesson types which incorporate all the skills demonstrated in the first part of the book. Part Three covers testing, teaching pronunciation, and using games, songsand rhymes. Part Four moves from basic pedagogy into a more communicative style of teaching
Keywords: english language - study and teaching